Exploring the effectiveness of various screening criteria used in gestational diabetes mellitus - S. Keerthana; Usha Devi Gopalan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Hyperglycemia during pregnancy leads to fatal maternal and perinatal outcomes. Gestational diabetes mellitus (GDM) is diagnosed by 75 grams oral glucose tolerance test at 24-28 weeks of gestational age as insulin resistance increases during the second trimester. Increased prevalence of diabetes mellitus, sedentary lifestyle, Family history of DM predisposes women, particularly the Indian women to develop GDM. Existence of multiple criteria like IADPSG (International association of diabetes and pregnancy study groups), WHO (World health organisation), ADA (The American diabetes association criteria, DIPSI (Diabetes in pregnancy study groups criteria) creates serious confusion in screening of GDM. Therefore, there is a need to find a effective single screening criteria.